Upper Broadcast Domination Number of Caterpillars with no Trunks - Bouchouika, Sabrina; Bouchemakh, Isma; Sopena, Eric (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
A broadcast on a graph G = (V,E) is a function f : V →0,…,diam(G) such that f(v) ≤ eG(v) for every vertex v ∈ V , where diam(G) denotes the diameter of G and eG(v) the eccentricity of v in G. Such a broadcast f is minimal if there does not exist any broadcast g≠f on G such that g(v) ≤ f(v) for all v ∈ V . The upper broadcast domination number of G is the maximum value of ∑ v∈V f(v) among all minimal broadcasts f on G for which each vertex of G is at distance at most f(v) from some vertex v with f(v) ≥ 1. In this paper, we study the minimal dominating broadcasts of caterpillars and give the exact value of the upper broadcast domination number of caterpillars with no trunks.